KIDDING PATTERN OF ASSAM HILL GOAT - Bohra, Pranjal; N. NAHARDEKA@gmail.com, N.; A. SALEQUE3, A.; R. G. SARMAH, R. G.; J. P. SARMA, J. P.; ANKUR DAS, ANKUR (Indian Journal of Animal Production and Management, 2017)
Data pertaining to 418 parturitions of Assam Hill Goat maintained at the adoptedvillages of AICRP on Goat Improvement, Goat Research Station, Burnihat were analysedto study the kidding pattern. The kidding was found to be distributed throughout theyear with the highest kidding in the post-monsoon season (31.34%). Month-wise kiddingrecords reveals that the highest and the lowest number of kidding was in the month ofSeptember (20.09%) and November (0.95%) respectively. The diurnal variation ofspontaneous live births showed uni-model distribution with maximum kidding between0600 to 1200 hours (56.46%) whereas the lowest incidence of kidding was recordedbetween 0.00 to 0600 hours. The percentage of single, twin and triplets were 60.76,34.93 and 4.31 respectively. In the present study the percentage of male kid born was50.50 per cent. The average birth weight of the male kids (1282.37gm) was higher thanthat of the female kids (1231.78 gm) at all types of birth (single, twins and triplets). Thedifference in birth weight between the sexes was non-significant.In rural Assam, goat plays an important role in the farming system as evidenced by thehigher annual growth rate (9.66 %) during the census year 2003-20078 in comparison toall India Annual Growth Rate per cent of 3.10.Key words : Assam Hill Goat, kidding pattern, diurnal variation.